2000
DOI: 10.1093/aje/152.12.1136
|View full text |Cite
|
Sign up to set email alerts
|

Early Child-Care and Preschool Experiences and the Risk of Childhood Acute Lymphoblastic Leukemia

Abstract: An infectious etiology for childhood acute lymphoblastic leukemia (ALL) has been suggested, yet few studies have focused on the role of early child care. Day-care histories were examined in a case-control study of ALL in New York State. Cases (n = 255) were diagnosed at one of four referral centers between 1980 and 1991; controls (n = 760) were randomly selected from livebirths in the 31 counties served by the referral centers. Self-administered questionnaires were mailed to the parents of cases and controls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
2
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 57 publications
1
62
2
5
Order By: Relevance
“…In support of this hypothesis, several studies have reported that early exposure to infection (van Steensel-Moll et al, 1986;Kaatsch et al, 1996;McKinney et al, 1999) is associated with a reduced risk of childhood ALL. However, contrary to what may be expected if this hypothesis is correct, we and several other investigators (Shaw et al, 1984;Shu et al, 1988;Kaye et al, 1991;McKinney et al, 1999;Schuz et al, 1999;Rosenbaum et al, 2000) did not find that later-born infants had a lower risk of ALL than first-born infants. Also we did not demonstrate a relationship between risk of ALL and number of children in the household, while being born into a household containing three or more adults appeared to be protective.…”
Section: Socioeconomic Status and Household Densitycontrasting
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, several studies have reported that early exposure to infection (van Steensel-Moll et al, 1986;Kaatsch et al, 1996;McKinney et al, 1999) is associated with a reduced risk of childhood ALL. However, contrary to what may be expected if this hypothesis is correct, we and several other investigators (Shaw et al, 1984;Shu et al, 1988;Kaye et al, 1991;McKinney et al, 1999;Schuz et al, 1999;Rosenbaum et al, 2000) did not find that later-born infants had a lower risk of ALL than first-born infants. Also we did not demonstrate a relationship between risk of ALL and number of children in the household, while being born into a household containing three or more adults appeared to be protective.…”
Section: Socioeconomic Status and Household Densitycontrasting
confidence: 99%
“…As in this study, some investigators have shown that higher socioeconomic position, is associated with higher risk of ALL (McWhirter, 1982;Kaye et al, 1991;Dockerty et al, 1999) but others have failed to observe this association (Shaw et al, 1984;van SteenselMoll et al, 1985van SteenselMoll et al, , 1986Shu et al, 1988;Kaatsch et al, 1996;McKinney et al, 1999;Rosenbaum et al, 2000) and some have found the opposite pattern, both for childhood ALL (Brondum et al, 1999;Dockerty et al, 1999) and infant leukaemia . In some of these studies subjects from higher socio-economic and better educational backgrounds are overrepresented among controls, reducing the ability to detect a positive association between socio-economic position and childhood ALL.…”
Section: Socioeconomic Status and Household Densitymentioning
confidence: 51%
“…To date, 13 case -control studies (Davis et al, 1988;Magnani et al, 1988;van Duijn et al, 1988;Shu et al, 1995;Petridou et al, 1997;Dockerty et al, 1999;McKinney et al, 1999;Schüz et al, 1999;Rosenbaum et al, 2000;Hardell and Dreifaldt, 2001; UK Childhood Cancer Study Investigators, 2001;Lancashire and Sorahan, 2003;Jourdan-Da Silva et al, 2004) have reported no association between breastfeeding and overall childhood leukaemia or ALL risk. Two of these previous studies restricted their analysis to children diagnosed between age 2 and 5 years and found no significant effect of breastfeeding on risk of leukaemia (Shu et al, 1995;UK Childhood Cancer Study Investigators, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large sample size, the CCG study did not provide adequate data to evaluate the relationship between daycare attendance and the risk of childhood ALL. In a more recent study that included ALL cases diagnosed at one of the four referral centres in western and central New York State, the odds ratio for children who stayed at home compared with those who attended daycare for greater than 36 months was 1.32 (95% CI: 0.70 -2.52); the odds ratios for 1 -18 and 19 -36 months of daycare were 1.74 (95% CI: 0.89, 3.42) and 1.32 (95% CI: 0.64, 2.71), respectively (Rosenbaum et al, 2000). When the analysis was restricted to B-lineage ALL, the magnitude of association increased.…”
Section: Epidemiologymentioning
confidence: 97%
“…Alexander suggested that daycare of the index child and of the siblings is probably the best available proxy measure of exposure to infections (Alexander et al, 1993). To date, daycare/preschool (referred to as 'daycare' from here on) attendance, along with other variables such as birth order and number of siblings, has been used as an indicator of exposure to common infections in several studies (Petridou et al, 1993(Petridou et al, , 1997Dockerty et al, 1999;Infante-Rivard et al, 2000;Neglia et al, 2000;Rosenbaum et al, 2000). However, the exposure assessment was crude in these studies and the results are inconsistent.…”
mentioning
confidence: 99%